Keeping track of time: Horizontal spatial biases for hours, days, and months. - Malyshevskaya, Anastasia; Miklashevsky, Alex; Fischer, Martin H.; Scheepers, Christoph; Shtyrov, Yury; Myachykov, Andriy (Memory & Cognition, 2024)
In many Western cultures, the processing of temporal words related to the past and to the future is associated with left and right space, respectively – a phenomenon known as the horizontal Mental Time Line (MTL). While this mapping is apparently quite ubiquitous, its regularity and consistency across different types of temporal concepts remain to be determined. Moreover, it is unclear whether such spatial mappings are an essential and early constituent of concept activation. In the present study, we used words denoting time units at different scales (hours of the day, days of the week, months of the year) associated with either left space (e.g., 9 a.m., Monday, February) or right space (e.g., 8 p.m., Saturday, November) as cues in a line bisection task. Fifty-seven healthy adults listened to temporal words and then moved a mouse cursor to the perceived midpoint of a horizontally presented line. We measured movement trajectories, initial line intersection coordinates, and final bisection response coordinates. We found movement trajectory displacements for left- vs. right-biasing hour and day cues. Initial line intersections were biased specifically by month cues, while final bisection responses were biased specifically by hour cues. Our findings offer general support to the notion of horizontal space-time associations and suggest further investigation of the exact chronometry and strength of this association across individual time units.